Effect of deficit irrigation on growth and yield of drip irrigated cabbage - RAJURKAR, G B; PATEL, NEELAM; RAJPUT, T B S; VARGHESE, CINI (The Indian Journal of Agricultural Sciences, 2015)
A field experiment was conducted on cabbage crop (var. Indo-American Hybrid Ramakrishna) during the winter season of 2010-11 in loamy soil of Water Technology Centre, Indian Agricultural Research Institute, New Delhi. The objective of the study was to evaluate the effect of three levels of irrigation, i.e. 60, 80 and 100% of crop evapotranspiration (ETc) and two types of drip irrigation systems, viz. pressure compensating (PC) and non-pressure compensating (NPC) drippers on the cabbage growth and yield. Rated discharge of PC and NPC drippers were 1.0 and 2.1 litres per hour (lph). Cabbage crop was sown in November 2013 at the spacing of 30cm (plant to plant) and 60cm (row to row). Leaf Area Index (LAI) was recorded at initial, developmental, mid-season and maturity stages while the root volume was determined at the maturity stage of crop growth. Under PC system, the LAI values of 0.59, 0.90 and 2.07 were recorded at initial, developmental and middle stage of crop, respectively. During maturity stage, NPC dripper showed higher LAI (2.61) as compared to PC drippers (2.57). Increased wetting depth under NPC system resulted in higher root depth (70 cm) and higher root volume. The maximum and minimum yields obtained in PC drippers were 91.2 and 83.33 t/ha, whereas in the plot having NPC drippers, maximum and minimum yields obtained were 61.48 and 53.70 t/ha, respectively. Yield obtained under 80 and 100 % ETc was not significantly different, however full application of water (100%) resulted in better yield. Thus, Pressure compensating drippers with discharge matching to crop water needs (1.0 lph) and irrigation at 80 % ETc is recommended as optimum practice for cabbage cultivation in loamy soils of northern India.